2007
DOI: 10.4321/s1130-01082007000500010
|View full text |Cite
|
Sign up to set email alerts
|

Paniculitis mesentérica: experiencia en nuestro centro

Abstract: La paniculitis mesentérica es un proceso inflamatorio crónico inespecífico del tejido adiposo mesentérico (1) con una forma de presentación muy variable. Para su diagnóstico definitivo suele ser necesario recurrir a la toma de biopsia de la lesión debido a la falta de especificidad de las pruebas radiológicas y la incapacidad de reconocer mucho de los factores precipitantes. Actualmente se reconoce que esta entidad presenta varios estadios evolutivos. Los criterios diagnósticos anato

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 38 publications
1
44
0
3
Order By: Relevance
“…Blood tests tend to be within the normal range. Neutrophilia, increased erythrocyte sedimentation rate or anemia have been reported occasionally in the retractile mesenteritis stage [6] . Some reports even go as far as stating that few or none of the patients with mesenteric panniculitis can be diagnosed correctly before operation [4,14] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Blood tests tend to be within the normal range. Neutrophilia, increased erythrocyte sedimentation rate or anemia have been reported occasionally in the retractile mesenteritis stage [6] . Some reports even go as far as stating that few or none of the patients with mesenteric panniculitis can be diagnosed correctly before operation [4,14] .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have indicated that the disease is more common in men, with a male/female ratio of 2-3:1, and several reports have indicated it to be more common in Caucasian men. Incidence increases with age, and pediatric cases are exceptional, probably because children have less mesenteric fat when compared to adults [6] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations